(untitled) - Powell, Robert (Singapore, 2004)
Singapore Architecture captures the architectural heritage of Asia's crossroads city. The early temples, chophouses and colonial monuments hold historical significance, while the modern skyline reflects Singapore's role as a 21st-century powerhouse. The recent work of local architects represents a unique and dynamic mix of cross-cultural influences, combining traditional Asian style with a thorough knowledge of modern architecture.
Keywords: Architecture, singapore